Perceptions, experiences and barriers to lifestyle modifications in first-generation Middle Eastern immigrants to Sweden: a qualitative study - Patricia Olaya-Contreras; Katarina Balcker-Lundgren; Faiza Siddiqui; Louise Bennet (BMJ Open)
Objective The prevalence of type 2 diabetes (T2D) among Iraqi immigrants to Sweden is high and partly related to sedentary physical activity and calorie dense food. The aim of the present study was to explore perceptions, experiences and barriers concerning lifestyle modifications (LSM) in Iraqi immigrants to Sweden at risk for T2D.Design A qualitative thematic analysis was conducted on data collected from gender-specific focus group interviews which took place during a culturally adapted randomised controlled intervention study addressing motivation to lifestyle change, self-empowerment, behavioural modifications and sociocultural barriers to LSM. Seven focus groups were held, with an interval of 1–4 weeks between January and May of 2015; each session lasted approximately 1.5 hours.Setting The city of Malmö, Sweden.Participants Out of 27 women and 23 men assigned to the intervention group, 19 women and 14 men who attended at least one focus group session were included in the study.Results Participants expressed awareness of the content of healthy lifestyle practices. They also expressed numerous social and cultural barriers to LSM connected to irregular meals, overeating, food and drinking preferences and family expectations. Overeating was described as a consequence of social and cultural norms and expectations and of poor mental well-being. Facilitators for reaching successful LSM were connected to family involvement and support.Conclusion Our study reports that facilitators for LSM are connected to presence of family support. Preventive actions addressing family involvement may benefit Middle Eastern immigrants at high risk for T2D to consider healthier lifestyles practices. Identification of sociocultural barriers and facilitators for LSM are crucial for successful health promotion in minority populations at risk for T2D.Trial registration Trial registration number: NCT01420198 for the MEDIM-study; Pre-results.